Characteristics of Porosity and Permeability of Ultra-High Temperature Perforated Damage Zone in Sandstone Targets - Xu, Changgui; Liang, Hao; Guo, Shusheng (Frontiers in Earth Science, 2022)
Perforating, as a widely-applied stimulation technology, is becoming incrementally important in unconventional oil/gas development, for it can effectively improve deep-lying HTHP low-porosity, low-permeability reservoirs, eliminate near-wellbore surface pollution and increase drainage area. Research on damage zone porosity directly reflects perforating performance. In order to study the damage zone of the sandstone target in regard of porosity and permeability, the paper involves the extraction of sandstone cores from the 3rd section of the Zhuhai Formation for the purpose of physically simulating an HTHP large-size target perforating experiment. After the simulation experiment, an automatic scanner was used to find the planar distribution characteristics of the porosity & permeability parameters of the 150℃ UHT perforation holes in the cores. The study involves two findings. First, the temperature has a minor effect on the hole depth and diameter in a specified scope. The hole depth decreases as the negative pressure increases and the depth decreases as the effective stress increases. Second, the UHP sandstone target is remarkably zone-specific in terms of the planar distribution of the hole porosity and permeability. The damage zone can be divided into the fracture zone, the transition zone, the compaction zone and the undisturbed zone. Besides, the zone permeability damage is quantified. The findings of this paper can effectively support research on COV numerical value simulation for HTHP perforation holes. Besides, they can support HTHP well perforating design and improve near-wellbore permeability enhancement and plug removal.